Asymptotic stability and bifurcations of 3D piecewise smooth vector fields - Carvalho, Tiago [UNESP]; Teixeira, Marco Antônio; Tonon, Durval José (Springer Nature, 2016)
The paper deals with the analysis of the behavior of a nonsmooth three-dimensional vector field around a typal singularity. We focus on a class of generic one-parameter families (Formula presented.) of Filippov systems and address the persistence problem for the asymptotic stability when the parameter varies near the bifurcation value (Formula presented.).
Keywords: Asymptotic stability; Cusp-fold singularity; Piecewise smooth vector fields